Prevalence of oral mucosal lesions and associated habits in Kashmir, India - Ain, Tasneem S.; Gowhar, Owais; Sultan, Saima; Tangade, Pradeep (International Journal of Research in Medical Sciences, 2017)
Background: A large number of factors may influence the conditions of oral-mucosa and regulate its thresholds against reactions to external irritations and insults. External damage to the tissues may be caused by infections and or other chemical, thermal and mechanical means or there may be some genetic factors involved. The aim of the study was to determine the prevalence of different oral habits and habit related oral lesions among the study population in Kashmir, India. Methods: The final study sample comprised of 7000 patients visiting 2 Government Hospitals in Srinagar and Pulwama district, Kashmir, India. All the selected subjects were examined for any oral mucosal lesions. The diagnosis of the lesion was made based on history, clinical features, according to standard guidelines and color atlas. Results: Prevalence of oral mucosal lesions was found to be 8%. Smoker’s palate was the most frequently found oral lesion comprising of 33.89% followed by oral lichen planus and leukoplakia (13.55% each). Other lesions included chemical burns, erythroplakia, OSMF and lichenoid reactions. Subjects were indulged into various habits; the most prevalent being the cigarette smoking (56.46%), followed by hukka and bidi smoking and smokeless tobacco. Conclusions: The prevalence of oral mucosal lesions was 8% among the study sample. Subjects were associated with various deleterious habits which were found more in males than females. This study helps in public awareness about the ill effects of oral habits and may motivate them in overcoming their indulgence.